Women Assistance in Fertile Age Couples in the use of Contraception as an Effort to Suppress Baby Booms During the Covid-19 Pandemic - Intan Yusita; Richa Noprianty; Ratna Dian Kurniawati; Linda Rofiasari; Antri Anriani (Jurnal Peduli Masyarakat, 2020)
The use of contraceptives in Indonesia during the Covid-19 pandemic has decreased by 35% to 47%. This resulted in the pregnancy rate increasing by 67 pregnancies from the previous year. In West Java, the pregnancy rate jumps by 10%. One of the efforts to suppress the spike in baby births is through the Keluarga Berencana (KB) program for couples with childbearing age. The aim of this community service is to provide knowledge about contraceptive tools and methods in suppressing baby booms. This community service method is in the form of interactive education based on information technology and offline interactive education. The target is 30 women of childbearing age couples aged between 15-45 who used contraception and did not make repeat visits during the Covid-19 pandemic. The implementation technique is divided into three stages, namely the first stage is to assess the level of understanding respondent with a pre-test use to google form, the second stage is to carry out counseling, family planning counseling program and introduction to the KB Klik application with offline and the third stage is to evaluate the material with a post test use to google form. The results of the activity showed an increase in knowledge of both contraceptive tools and methods by 53.4%. With the increasing knowledge of mothers about family planning tools and methods, it is hoped that it can influence the attitudes of mothers in choosing and using the right contraceptives so that it is expected to limit the number of child births and reduce the impact of baby booms.